'Dazed and Confused!' Context and Social Disconnect in the Time of Pandemic. Issue 3 (December 2021) - Piguet, Olivier
Abstract: Humans are social animals. Our sense of identity and 'self' is defined in part by the roles we perform in the social groups to which we belong. This article discusses some of the variables that contribute to our sense of self, including language, place of origin, education and shared social norms. It also outlines some of the general mechanisms that underpin our various social networks. In its final part, this article reviews the impact of social isolation, such as that happened during the COVID pandemic, on these social mechanisms and the resulted disruption of psychological wellbeing in individuals diagnosed with dementia.